REAACH-ID 2023 - REpresentation Advances And Challenges. AI-XR Connections (diségno, 2023)
The fourth edition of the REAACH-ID symposium, coordinated by Andrea Giordano (University of Padua), Roberta Spallone (Politecnico di Torino) and Michele Russo (Sapienza Università di Roma), was held in telematic mode from 10 to 11 October 2023 (fig. 1). Resuming the debate addressed in previous edi- tions, on the challenges that the new digital methods offer to experts and scholars in the field of representation, the event aimed to focus attention on the possibility of connecting ‘extended” reality (XR) technologies –which includes augmented reality (AR), virtual reality (VR) and mixed reality (MR)– with the disciplines that employ artificial intelligence (AI). In this sense, the call proposed an exposure, in terms of  applications and experimentation, to the worlds of tangible and intangible cultural heritage, architectural, environmental, infrastructural and product design, and education, as a place of higher education as well as a tool for educational enhancement. [read more]